Chiral phases of fundamental and adjoint quarks - Natale, A. A. [UNESP] (AIP Publishing, 2016)
We consider a QCD chiral symmetry breaking model where the gap equation contains an effective confining propagator and a dressed gluon propagator with a dynamically generated mass. This model is able to explain the ratios between the chiral transition and deconfinement temperatures in the case of fundamental and adjoint quarks. It also predicts the recovery of the chiral symmetry for a large number of quarks (nf ≈ 11-13) in agreement with lattice data.
Keywords: Chiral symmetry; Confinement; Dynamical gluon mass